Baicalein suppresses repeat tau fibrillization by sequestering oligomers - Sonawane, Shweta Kishor; Balmik, Abhishek Ankur; Boral, Debjyoti; Ramasamy, Sureshkumar; Chinnathambi, Subashchandrabose (Archives of Biochemistry and Biophysics, 2019)
Alzheimer's disease (AD) is a neurodegenerative disorder caused by protein misfolding, aggregation and accumulation in the brain. A large number of molecules are being screened against these pathogenic proteins but the focus for therapeutics is shifting towards the natural compounds as aggregation inhibitors, mainly due to their minimum adverse effects. Baicalein is a natural compound belonging to the class of flavonoids isolated from the Chinese herb Scutellaria baicalensis. Here we applied fluorescence, absorbance, microscopy, MALDI-TOF spectrophotometry and other biochemical techniques to investigate the interaction between Tau and Baicalein in vitro. We found the aggregation inhibitory properties of Baicalein for the repeat Tau. Overall, the potential of Baicalein in dissolving the preformed Tau oligomers as well as mature fibrils can be of utmost importance in therapeutics for Alzheimer's disease.
Keywords: Alzheimer disease; Baicalein; Microtubule assembly; Paired helical filaments; Protein aggregation; tau protein

Basic limonoid modulates chaperone-mediated proteostasis and dissolve Tau fibrils - Gorantla, Nalini Vijay; Das, Rashmi; Chidambaram, Hariharakrishnan; Dubey, Tushar; Mulani, Fayaj A.; Thulasiram, V. Hirekodathakallu; Chinnathambi, Subashchandrabose (Scientific Reports, 2020)
The Alzheimer's disease pathology is associated with accumulation of intracellular neurofibrillary tangles and extracellular senile plaques. The formation of initial nucleus triggers conformational changes in Tau and leads to its deposition. Hence, there is a need to eliminate these toxic proteins for proper functioning of neuronal cells. In this aspect, we screened the effect of basic limonoids such as gedunin, epoxyazadiradione, azadirone and azadiradione on inhibiting Tau aggregation as well as disintegration of induced Tau aggregates. It was observed that these basic limonoids effectively prevented aggregates formation by Tau and also exhibited the property of destabilizing matured Tau aggregates. The molecular docking analysis suggests that the basic limonoids interact with hexapeptide regions of aggregated Tau. Although these limonoids caused the conformational changes in Tau to beta-sheet structure, the cytological studies indicate that basic limonoids rescued cell death. The dual role of limonoids in Tau aggregation inhibition and disintegration of matured aggregates suggests them to be potent molecules in overcoming Tau pathology. Further, their origin from a medicinally important plant neem, which known to possess remarkable biological activities was also found to play protective role in HEK293T cells. Basic limonoids were non-toxic to HEK293T cells and also aided in activation of HSF1 by inducing its accumulation in nucleus. Western blotting and immunofluorescence studies showed that HSF1 in downstream increased the transcription of Hsp70 thus, aggravating cytosolic Hsp70 levels that can channel clearance of aberrant Tau. All these results mark basic limonoids as potential therapeutic natural products.

Baicalein inhibits heparin-induced Tau aggregation by initializing non-toxic Tau oligomer formation - Sonawane, Shweta Kishor; Uversky, Vladimir N.; Chinnathambi, Subashchandrabose (Cell Communication and Signaling, 2021)
Background: Amyloid aggregate deposition is the key feature of Alzheimer's disease. The proteinaceous aggregates found in the afflicted brain are the intra-neuronal neurofibrillary tangles formed by the microtubule-associated protein Tau and extracellular deposits, senile plaques, of amyloid beta (A beta) peptide proteolytically derived from the amyloid precursor protein. Accumulation of these aggregates has manifestations in the later stages of the disease, such as memory loss and cognitive inabilities originating from the neuronal dysfunction, neurodegeneration, and brain atrophy. Treatment of this disease at the late stages is difficult, and many clinical trials have failed. Hence, the goal is to find means capable of preventing the aggregation of these intrinsically disordered proteins by inhibiting the early stages of their pathological transformations. Polyphenols are known to be neuroprotective agents with the noticeable potential against many neurodegenerative diseases, such as Alzheimer's, Parkinson's, and Prion diseases. Methods: We analyzed the capability of Baicalein to inhibit aggregation of human Tau protein by a multifactorial analysis that included several biophysical and biochemical techniques. Results: The potency of Baicalein, a polyphenol from the Scutellaria baicalensis Georgi, against in vitro Tau aggregation and PHF dissolution has been screened and validated. ThS fluorescence assay revealed the potent inhibitory activity of Baicalein, whereas ANS revealed its mechanism of Tau inhibition viz. by oligomer capture and dissociation. In addition, Baicalein dissolved the preformed mature fibrils of Tau thereby possessing a dual target action. Tau oligomers formed by Baicalein were non-toxic to neuronal cells, highlighting its role as a potent molecule to be screened against AD. Conclusion: In conclusion, Baicalein inhibits aggregation of hTau40 by enhancing the formation of SDS-stable oligomers and preventing fibril formation. Baicalein-induced oligomers do not affect the viability of the neuroblastoma cells. Therefore, Baicalein can be considered as a lead molecule against Tau pathology in AD.
Keywords: Alzheimer's disease; Baicalein; Tau dissolution; Tau inhibition; Tau Oligomers

Bacopa monnieri reduces Tau aggregation and Tau-mediated toxicity in cells - Dubey, Tushar; Kushwaha, Preeti; Thulasiram, H. V.; Chandrashekar, Madhura; Chinnathambi, Subashchandrabose (International Journal of Biological Macromolecules, 2023)
Alzheimer's disease is a neurodegenerative disease characterized by progressive memory loss and behavioral impairments. In the present study, the ethanolic extract of Bacopa monnieri was studied for its potency to inhibit Tau aggregation and rescuing of the viability of Tau-stressed cells. Bacopa monnieri was observed to inhibit the Tau aggregation in vitro. The cells exposed to Bacopa monnieri were also observed to have a low level of ROS and caspase-3 activity. The immunoblot and immunofluorescence analysis showed that Bacopa monnieri acts as an antioxidant and restored the Nrf2 levels in Neuro2a cells. Bacopa monnieri treatment to Neuro2a cells was observed to reduce the phospho-Tau load in formaldehyde-stressed cells. Furthermore, the treatment of Bacopa monnieri reduced the phosphorylation of GSK-3 beta in formaldehyde-stressed cells. Ran and NUP358 are the key proteins involved in nuclear transport. It was observed that formaldehyde treatment impaired the nuclear transport by missorting the NUP358 arrangement in Neuro2a cells. On the contrary, Bacopa monnieri treatment restored the NUP358 arrangement in cells. The overall results of the present study suggested that Bacopa monnieri could be considered a potent herb against Tau phosphorylation and Tau aggregation, which projects it as a promising formulation for Alzheimer's disease.
Keywords: Bacopa monnieri; GSK-3 beta; Nrf2; Nuclear transport; NUP358; Tau Aggregation; Tau phosphorylation